Al-Dakhil Pada Hadis Mawdhu’ Seputar Asbàbun Nuzùl: (Suatu Penelusuran Terhadap Asbàbun-Nuzùl Karya al-Wahidi) - Nasution, Khairul Bahri (Program Studi Ilmu Al-Qur'an dan Tafsir STAIN Mandailing Natal, 2024)
Knowledge about asbàbun-nuzùl is one of the most important things to know, because interpreting and expressing the meaning of a verse cannot be done without knowing the chronology that caused the revelation of that verse. The scholars stated that the best way to know asbàbun-nuzùl is through authentic narratives. However, in reality there is a lot of literature surrounding asbàbun-nuzùl, both material-substantial literature which contains mawdhu' hadiths which fall into the classification of al-dakhîl in the field of tafsir science. Among the literature regarding asbàbun-nuzùl that is often referred to is the work of Abu Hasan 'Ali al-Wahidi an-Naisabùriy. In his book, he has emphasized his own opinion that